What Do Middle Grades Preservice Teachers Believe about Writing and Writing Instruction?. Issue 2 (7th February 2019) - Hodges, Tracey S.; Wright, Katherine Landau; McTigue, Erin
Abstract: After third grade, students' motivation and enjoyment of writing begins to wane, and this trend continues through most of their education. Middle grade students especially need high-quality writing instruction; however, many teachers report feeling inadequately prepared to teach writing. To combat these issues, teacher preparation programs should understand how their preservice teachers feel about writing and teaching writing. The present study surveyed 150 middle grade preservice teachers to determine their self-efficacy beliefs about writing and writing instruction. Results indicate that preservice teachers valued writing, but did not feel confident with many specific aspects of writing instruction.